Parental acceptance of silver fluoride as a treatment option for carious lesions among South African children with special health care needs - Potgieter, N.; Noordien, N.; Mulder, R.; Peck, C.; Groisman, S. (Frontiers in Oral Health, 2023)
Providing dental care for children with neurological special health care needs, including Down syndrome, Cerebral palsy and Autism spectrum disorders, is challenging. They often require repeat exposure to sedation or general anaesthesia for routine dental care. 51 parents of children with special needs completed a questionnaire regarding the acceptance of Silver Fluoride as a treatment option. Background: Silver Diamine Fluoride has become popular as a minimally invasive treatment option for providing oral health care to young or uncooperative children. Silver Fluoride (SF) is a newer development with similar but improved properties. The aim was to determine the acceptance of SDF/SF as treatment option for Children with Special Health Care Needs (CSHCN), including Down Syndrome, Autism Spectrum Disorder and Cerebral Palsy. Methods: 51 Parents of CSHCN completed a questionnaire on the overall acceptance of SF; aesthetic concerns related to the location of application; the use of SDF as an alternative to general anesthesia; and the composition of SF. Results: The use of SF on posterior teeth were more acceptable (70,59%) as opposed to its application to anterior teeth (50,98%). Parents generally agreed/ strongly agreed to the use of SF to reduce infection and pain (82%); to avoid treatment under GA (26,70%); and to avoid an injection (78%). 64% of parents indicated their agreement in using SF because it has a reduced cost when compared to a conventional restoration. Majority of parents were in agreement to use SF even if it contains Fluoride (84%) and Silver (78%). Conclusion: The use of SF, as treatment option for caries, was well accepted by South African parents of CSHCN. Shared decision making should be applied when considering SF as treatment option for CSHCN.